2000
DOI: 10.1128/aem.66.9.3974-3980.2000
|View full text |Cite
|
Sign up to set email alerts
|

Dissolution of Xylose Metabolism in Lactococcus lactis

Abstract: Xylose metabolism, a variable phenotype in strains of Lactococcus lactis, was studied and evidence was obtained for the accumulation of mutations that inactivate the xyl operon. The xylose metabolism operon (xylRAB) was sequenced from three strains of lactococci. Fragments of 4.2, 4.2, and 5.4 kb that included the xyl locus were sequenced from L. lactis subsp. lactis B-4449 (formerly Lactobacillus xylosus), L. lactis subsp. lactis IO-1, and L. lactis subsp. lactis 210, respectively. The two environmental isola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0
3

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 48 publications
2
29
0
3
Order By: Relevance
“…Another explanation for this finding is that L. lactis KF147 XylR is different from XylR transcriptional regulators found in other Firmicutes (62). L. lactis KF147 XylR is a member of the AraC family of transcriptional regulators, whereas XylR proteins from related bacteria are classified as ROK (repressor, open reading frame, kinase) family regulators (62,63). In E. coli, expression of the araBAD operon is highly induced upon exposure to arabinose through a "light switch"-type mechanism of AraC (64).…”
Section: Discussionmentioning
confidence: 87%
“…Another explanation for this finding is that L. lactis KF147 XylR is different from XylR transcriptional regulators found in other Firmicutes (62). L. lactis KF147 XylR is a member of the AraC family of transcriptional regulators, whereas XylR proteins from related bacteria are classified as ROK (repressor, open reading frame, kinase) family regulators (62,63). In E. coli, expression of the araBAD operon is highly induced upon exposure to arabinose through a "light switch"-type mechanism of AraC (64).…”
Section: Discussionmentioning
confidence: 87%
“…1). An open reading frame with homology to the gene for xylose kinase (XylB) was located downstream of xylA in the same orientation, indicating that the genes for xylose utilization by L. reuteri 100-23 were organized in an operon, as described for several other gram-positive bacteria (9). Sequence analysis of the promoter region of met revealed that gene expression is likely to be transcriptionally regulated by the T box mechanism (12).…”
Section: Resultsmentioning
confidence: 94%
“…(4)-via a combination of both pentose phosphate and the EM pathway. Thus, the most common initial reactions of bacterial xylose catabolism involve xylose isomerase and xylulose kinase (4,13,23,29,36).…”
mentioning
confidence: 99%